2017
DOI: 10.1080/13803395.2017.1301391
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive complaints in women with fibromyalgia: Are they due to depression or to objective cognitive dysfunction?

Abstract: Cognitive complaints are very frequent in patients with fibromyalgia, and these are related to functional and cognitive impairment as well as to depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 46 publications
4
33
2
2
Order By: Relevance
“…Theoretical models and empirical observations suggest negative impact of aversive mood states on cognition ( Eysenck et al, 2007 ; Snyder, 2013 ). Accordingly, various studies demonstrated stronger cognitive impairments in FMS patients exhibiting more severe symptoms of depression and anxiety ( Hassett et al, 2008 ; Munguía-Izquierdo et al, 2008 ; Gelonch et al, 2016 , 2017 ). However, some FMS studies directly comparing the impacts of depression and anxiety with the impact of pain severity revealed the closest connection between pain and performance ( Reyes del Paso et al, 2012 , 2015 ; Duschek et al, 2013 ; Weiss et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models and empirical observations suggest negative impact of aversive mood states on cognition ( Eysenck et al, 2007 ; Snyder, 2013 ). Accordingly, various studies demonstrated stronger cognitive impairments in FMS patients exhibiting more severe symptoms of depression and anxiety ( Hassett et al, 2008 ; Munguía-Izquierdo et al, 2008 ; Gelonch et al, 2016 , 2017 ). However, some FMS studies directly comparing the impacts of depression and anxiety with the impact of pain severity revealed the closest connection between pain and performance ( Reyes del Paso et al, 2012 , 2015 ; Duschek et al, 2013 ; Weiss et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study incorporating objective measures of cognitive performance, depression together with working memory, and everyday physical functioning predicted (32% of the total variance) subjective cognitive complaints (Gelonch et al., ), indicating that perceived subjective dyscognition may not only be partially related to objective cognitive impairments but also to affective symptomatology. Regarding the contributing role of depression to fibrofog in our results, in the known‐groups validity analyses, significant differences in mean MISCI scores were found among samples of patients with FM with or without comorbid depression and a clinical comparative group without FM suffering residual depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, higher catastrophizing or pain‐related fear/anxiety can be related to more difficulties in diverting attention away from a painful event, so limiting the available attentional resources (Roth, Geisser, Theisen‐Goodvich, & Dixon, ). In previous studies in patients with chronic pain or FM, despite heterogeneous results, cognitive complaints have been linked to pain intensity, depression (Gelonch, Garolera, Valls, Rosselló, & Pifarré, ; McCracken & Iverson, ), anxiety, sleep problems, and fatigue (Kravitz & Katz, ). As proposed by Williams et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America alone, chronic pain costs over $650 billion in health care and lost productivity [ 3 ]. Fibromyalgia is a complex clinical disorder characterized by chronic widespread pain that is also associated with sleep disturbance, fatigue, irritable bowel syndrome, depressed mood, and, possibly cognitive dysfunction [ 4 , 5 ]. Patients suffering with fibromyalgia very frequently report functional disability and impaired quality of life [ 6 ]; furthermore, fibromyalgia is a common disorder estimated to affect 1.6% of men and 4.9% of women [ 7 ].…”
Section: Introductionmentioning
confidence: 99%